Decomposition properties of PVA/graphene composites during melting-crystallization. (September 2015) - Li, Chengpeng; Hou, Tingting; She, Xiaodong; Wei, Xiaoyi; She, Fenghua; Gao, Weimin; Kong, Lingxue
Abstract: The thermal decomposition of PVA and PVA composites during the melting-crystallization process is still unclear due to indistinct changes in chemical compositions. Using graphene as a model, the decomposition properties of PVA and PVA–graphene composites were systematically analyzed under multiple melting-crystallization cycles. And a series of isothermal decomposition experiments around the melting-crystallization temperature were carried out to simulate the corresponding decomposition kinetics. Based on multiple cycle melting-crystallization, the weight loss of PVA and PVA/graphene composites was successfully quantified. Further morphology investigation and chemical structure analysis indicated that the decomposition was non-uniformly distributed, rendering the possibility of crystallization for PVA and PVA/graphene composites after multiple heating–cooling cycles. In addition, isothermal decomposition analysis based on reduced time plot approach and model-free iso-conversional method indicated that Avrami-Eroffev model could well match the decomposition process of the neat PVA and PG-0.3 composite, while the Avrami-Eroffev and first order models could precisely forecast the decomposition of PG-0.9 composite. Both analyses during multiple cycle melting-crystallization and isothermal decomposition demonstrated that graphene served as decomposition accelerator in the whole thermal decomposition process, and particularly the decomposition of neat PVA and PVA/graphene composites was highly related to the band area ratios of C–H and O–H vibrations in Fourier transform infrared (FTIR) spectrum. Graphical abstract: Highlights: The weight loss of PVA and PVA/graphene composites during melting-crystallization process is firstly quantified. The decomposition decreases melting and crystallization enthalpies, but enhances glass transition temperature. The thermal decomposition during melting-crystallization is not homogeneous. The isothermal decomposition kinetics of PVA and PVA/graphene composites is proposed.